Evaluating the Effect of Fire on Cultivated Tropical Peat Properties: Lessons Learned from Observation in East Kutai Peatlands: The effect of fire on cultivated tropical peat properties - Heru Bagus Pulunggono; Moh Zulfajrin; Nabila Hanifah; Lina Lathifah Nurazizah (Faculty of Agriculture, Tompotika Luwuk University, 2022)
Fire and its associated impact highly affect peatland, particularly the peat properties, the plant cultivated above it, and its surrounding environment. Despite much research focused on fire monitoring or susceptibility assessments, peat consumption during fire occurrence, emissions from burned peat, and rehabilitation or restoration of burned peat, little attention is given to studying the changes of peat bio-physicochemical after burning. This small-scale study aims to examine the fire’ effect on the upper 30 cm of peat’s bio-physicochemical properties two months after being burned, using unburned peat as a reference. The result of this study indicated that fire-affected peat at all of our sampling depths. The impacted changes on peat chemical variables were varied. This study also found that sampling methods, fire magnitude and severity, peat physicochemical properties, laboratory determination, and statistical analyses were paramount in examining the fire effect on peat properties. This study also promotes the combination approach that represents both local and global phenomena to analyze and interpret the change of burned peat properties from its initial unburned state. More efforts are required to verify the initial results reported in this study and to gain in-depth information concerning the intricate relationships of organic materials, climate, hydrology, and vegetation across spatial and temporal scales in cultivated tropical peat as affected by fire events.